The characteristic of anxiety disorder among medical students of Universitas Udayana, Bali, Indonesia in the 2019 period - Kuganesh Ravichandran; Dewa Ayu Shintya Dewi; I Wayan Aryabiantara (DiscoverSys Inc., 2020)
Background: Anxiety is a normal stress reaction and can be beneficial in some dangerous situations. The symptoms are individual, whereas most of them include restlessness, feeling keyed up on edge, being easily fatigued, difficulty concentrating, irritability, muscle tension, and sleep disturbance. This study aims to determine the characteristic of anxiety disorder among medical students of Universitas Udayana, Bali, Indonesia, in the 2019 periodMethods: A cross-sectional study was conducted among 75 medical students who met the inclusion criteria in this study. The characteristic of anxiety disorders depicted in this study was the prevalence, anxiety severity, characteristic of anxiety, and possible stressors. Depression Anxiety and Stress Scale- 21 (DASS-21) used to assess anxiety among medical students. Data were analyzed descriptively using SPSS version 21 for Windows and presented in percentages.Results: From 75 medical students, 11 (14.67%) students were batch 2016, 25 (33.33%) students were batch 2017, and 39 (52.0%) students were batch 2018. Based on the DASS-21 score, there were 53 students (70.7%) experienced anxiety. According to the severity of anxiety, we found that the vast majority of students (45.3%) belong to the extremely severe anxiety group, followed by severe anxiety (20.8%), moderate anxiety (15.1%) and mild anxiety (11.3%).Conclusion: The characteristic of anxiety disorder among medical students were predominant by the severe anxiety group based on the DASS-21 score.